PEMAKNAAN PRIMBON BETALJEMUR ADAMMAKNA PADA ARSITEKTUR JAWA DITINJAU DARI ASPEK PSIKOLOGIS - Josephine Roosandriantini (Nature: National Academic Journal of Architecture, 2023)
The concept of a house for the Javanese is to make a home or tame, pomahan (at home in the house), the house’s yard. Judging from the concept of a house, it is not just a place to live or a place of activity, but it is related to the psychology of comfort of the owner. Javanese architecture in ancient times was obtained by a petungan (calculation) system in a written document called Primbon, but the mindset of today’s society assumes that Primbon is something occult, unscientific, and knowledgeable. If we use our point of view as Javanese people, in the field of Primbon architecture, it contains prohibitions that are indirectly a choice that has consequences for the homeowner. If viewed from the point of view of Psychology, it can be shown that these prohibitions have consequences that can impact the nature, behavior, and so on related to the psyche of the homeowner. This study aims to interpret the meaning of the Primbon Betalsun Adammakna, considered a scientist heresy, that Primbon can be said as a scientific guideline and is related to architecture and psychology. The research method is descriptive qualitative, collecting measurement data from field studies (Javanese architecture) and carrying out the meaning of calculations with the Primbon Betaljemur Adammakna. The research object used in this study is a residential house in Gunung Kidul, D.I. Yogyakarta. The research results prove that Primbon Betaljemur Adammakna is scientific knowledge in building Javanese architecture.